TÜRKÇEDEKİ ADLAŞTIRICILARIN SINIFLANDIRILMASI VE SÖZDİZİMSEL ÇÖZÜMLEMESİ: MİNİMALİST BİR YAKLAŞIM - Şeker, Emrullah (My University, 2015)
Bu çalışmanın amacı Türkçedeki Ad fiil, Sıfat fiil ve Zarf fiillerin biçimbilimsel ve sözdizimsel çözümlemesine Minimalist Program çerçevesinde çözüm önerileri getirmektir. Bu adcıl özelliklere sahip olan zaman-çekimsiz fiil biçimlerinin sözdizimsel çözümlemeleri her zaman oldukça tartışmalı olmuştur. Bunların ad öbeği (AÖ), belirleyici öbeği (BÖ), çekimsiz zaman öbeği (ZAMÖ), çekim öbeği (ÇEKÖ), sözlükçede türetme ekleriyle türetilen eylemlerin öbek başı olduğu eylem öbekleri (EÖ) veya adlaştırıcı öbeği (ADÖ) v.b. olduklarını iddia eden farklı çalışmalar bulunmaktadır. Ayrıca, aynı biçimbirimlerin aynı dilde farklı kategoriler altında farklı işlevlerde bulunması da bu adcıl özellik taşıyan biçimbirimsel öbek görüşlerin ortaya atılmasına sebep olmuştur. Bu bağlamda, tümce içerisinde fiillerin özne, tümleç, eklenti (zarf) veya niteleyici (sıfat) olarak kullanılmasını sağlayan, adcıl özelliklere sahip öbekler kuran ve işlevsel bir kategori oluşturan biçimbirimler Minimalist Program çerçevesinde incelenmiş, sorgulanmış ve sınıflandırılmıştır. Öncelikle, Türkçedeki çekim ve türetme eklerinin biçimbilimsel ve sözdizimsel özellikleri adcıl özellik taşıyan işlevsel bir kategoriyi oluşturan biçimbirimlerle türetme ekleri arasında bir ayrım yapmak için karşılaştırılmış ve karşıtlaştırılmıştır. Daha sonra, zaman, Genişletilmiş Yansıtma İlkesi (GYİ) ve uyum gibi dilbilgisel özellikleri belirten biçimbilimsel özellikler temel alınarak, adcıl özelliklere sahip tüm biçimbirimler 'adlaştırıcılar', 'türetme ekleri' ve 'çekimsiz zaman öbeği' kurucuları arasındaki ayrımı açıkça ortaya koyacak şekilde 'adlaştırıcılar' ve 'çekimsiz zaman öbeği' kurucuları olarak kategorize edilmiştir. Son olarak, bu öbekleri sözlüksel bir fiilin başını çektiği bir EÖ veya sözlükçede türetilen bir AÖ olarak kabul etmek yerine, bu çalışma adlaştırıcıları adlaştırıcı (AD) olarak kategorize etmekte ve bu adlaştırıcıların baş konumunda olduğu öbek yapılar için ADÖ çözümlemesi önermektedir. Bu çalışma ayrıca geleneksel betimleyici ve kuralcı Türkçe dilbilgisinde tanımlanan çekimsel biçimbirimlerin ED kavramlarıyla sınıflandırılmasına katkı sağlamaktadır. sınıflandırılmasıyla ilgili olarak öne sürülen tartışmalı görüşler dikkate alındığında, bu çalışma sadece Türkçe biçimbilgisi içerisinde yer alan bu yapıların sözdizimsel çözümlemesi için değil, ayrıca adcıl özellik taşıyan biçimbirimlerin sınıflandırılması için de önemli öneriler sunmaktadır

In this study which aims to analyze Turkish inflectional morphology in order to identify nominalizers and their syntactical representation in terms of the MP and question, explain and recategorize nominal affixes, all of which are categorized as nominalizers in traditional Turkish grammar through UG terms, we analyzed morphological and semantic properties of Turkish inflectional affixes having nominal features using substitution technique and then categorized them into T or Nom heads in order to make a clear distinction between nominalizers, derivational morphology and inflectional T. In this context, we initially compared and contrasted derivational noun suffixes (e.g. -Im, -Aç, -gIç, -cE) and inflectional nominalizers (e.g. TR: -mA) through substitution. From these comparisons, it was found out that while verbs suffixed by inflectional nominalizers may have complements, verbs suffixed by derivational noun suffixes cannot have complements. It was also found out that while derived nouns cannot be modified by adverbs but by adjectives, nominalised verbs cannot be modified by adjectives but by adverbs, by which we can easily distinguish derivational noun affixes from inflectional nominalizer heads. These properties demonstrated that verbs inflected by the nominalizer -mA functions as complements or subject specifiers (i.e. internal or external arguments) in the syntax. On the other hand, the verbs nominalised by -(y)An, -AcAk and -mIş modify nouns, while verbs inflected by the nominalizers -ArAk and -IncA are adjoined to verbs. In addition, nominalizers were also distinguished from inflectional infinite (INF) tense (T) constituents projecting TPs, requiring overt or null (PRO) subject specifier and carrying tense (i.e. priori or irrealis future) features. Accordingly, the infinitival -mAk could be distinguished from nominalizers in that it cannot be assigned cases and carries an ‘irrealis tense’ feature with a null PRO subject, projecting ‘a complement clause’ known as a ‘control clause’, which gave us enough evidence to categorize them as infinite T constituents. Furthermore, verbs headed by -dIk and -mA were found demonstrating similar properties in terms of their [EPP] and “factive” (e.g. -dIk) or “irrealis” (e.g. -mA and -AcAk) tense features. It was also pointed out that infinite T heads are in agreement with their external arguments assigned GEN case (e.g. Ali’nin yaptığı/Ali-GEN have-INF-3SgP). It was also found that aspectual heads such as perfect (PER), progressive (PROG) or habitual (HAB) are headed by finite or infinite T heads but by nominalizers, which I referred as another criterion to discriminate between nominalizers and infinite T constituents. Through the comparative and contrastive analyses of the properties of nominal affixes in Turkish, it was concluded that Turkish operates a functional affixal c-selectional (selecting lexical category of verbs) category of nominalizers (i.e. -mA, -(y)An, -ArAk and -IncA ) having nominal features but [EPP]. Considering the data we obtained from these categorizations, I concluded that a functional category of nominalizers having limited number of constituents is needed to be represented in the syntax. This functional category makes verbs function as nouns, adjectives or adverbs externally but allows them to have complements or adjuncts internally. Therefore, rather than regarding these structures as VPs headed by a lexical verb, or NPs derived in the lexicon, it was found plausible to suggest a “nominalizer phrase” (NomP) headed by a functional affixal head called “nominalizer” (Nom) selecting verbs. Accordingly, the category of Nom which is headed by an affixal nominalizer head was assumed to carry a STRONG V feature, triggering the raising of the complement to attach, checking the matching features and forming the NomP Ving. Different from an infinite TP, a NomP may not project an external argument, or a specifier subject, to form an extended NomP. Therefore, in this context, the nominalizer heads and their syntactical positions as specifiers, complements, modifiers and adjuncts were analysed on tree diagrams through suggestions by the MP. NomPs serving as internal arguments such as a verb or postposition complement and external arguments, or subject specifiers, were analyzed under a D head, forming DPs, which may also explain case assignment in nominalised structures. As for the NomPs having an adjectival function, on the other hand, verbs headed by the nominalizer -(y)An, perfective and prospective aspectual heads -mIş and -AcAk were also analyzed as modifier NomPs extending the projection to form an extended NP which is finally headed by a D, forming a DP. As for the adjunct NomPs, nominalizers such as -ArAk and -IncA were analyzed as NomPs which are adjoined to verbs as adjuncts, projecting an external argument but carrying agreement features, finally forming extended VPs. However, it was also found that adverbial NomP headed by -IncA does not carry agreement (i.e. [Per] and [Num]) features although it projects an external argument as a subject specifier as in the case of complement NomPs since it is not headed by a higher D.
CATEGORIZATION AND SYNTACTICAL ANALYSIS OF NOMINALIZERS IN TURKISH: A MINIMALIST APPROACH